Personality in a Hierarchical Model of Psychopathology. (January 2019) - Widiger, Thomas A.; Sellbom, Martin; Chmielewski, Michael; Clark, Lee Anna; DeYoung, Colin G.; Kotov, Roman; Krueger, Robert F.; Lynam, Donald R.; Miller, Joshua D.; Mullins-Sweatt, Stephanie; Samuel, Douglas B.; South, Susan C.; et al.
The categorical model of classification in the fifth edition of the Diagnostic and Statistical Manual of Mental Disorders is sorely problematic. A proposed solution is emerging in the form of a quantitative nosology, an empirically based dimensional organization of psychopathology. More specifically, a team of investigators has proposed the Hierarchical Taxonomy of Psychopathology (HiTOP). The purpose of this article is to discuss the potential role, importance, and implications of personality within the HiTOP dimensional model of psychopathology. Suggested herein is that personality provides a foundational base for the HiTOP dimensional model of psychopathology. Implications concern the potential value of the early assessment of and screening for personality as well as the development of protocols for the treatment of personality trait domains, which may in turn contribute to substantial improvements in quality of life as well as mental and physical health.